1997
DOI: 10.1177/074193259701800405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Technology Use in California's Special Education Programs

Abstract: This study investigated changes in technology use in california's special education programs between the late 1980s and mid-1990s. two groups representing districts that participated in an earlier study were surveyed: special education administrators ( n = 149) and special educators who routinely use technology in instruction ( n = 189). Results suggest that computers and other technologies are more available today and used more often by administrators, teachers, and students with disabilities. Students are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…The more access and use they had of the CAI, whether at school or at home, the more their understanding of math concepts increased. This supports the findings of Lewis (1997) that technology lends towards improved delivery in instruction and thus positively affects students' learning.…”
Section: Journal Of Research On Technology In Educationsupporting
confidence: 89%
See 3 more Smart Citations
“…The more access and use they had of the CAI, whether at school or at home, the more their understanding of math concepts increased. This supports the findings of Lewis (1997) that technology lends towards improved delivery in instruction and thus positively affects students' learning.…”
Section: Journal Of Research On Technology In Educationsupporting
confidence: 89%
“…Both Lewis (1997) and Avitabile (1996) found similar reactions with the integration of technology into learning. That is, they found improvement in student attitude and confidence contributing to enhanced student learning.…”
Section: Journal Of Research On Technology In Educationsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, most applications incorporate hardware and software targeted at general audiences, rather than products designed specifically for persons with learning disabilities. For example, in one set of studies in which special education teachers identified the software they had found most valuable for the students with learning disabilities they served (Lewis, 1997;Lewis, Harrison, Lynch, & Saba, 1994), almost all of the top-rated programs were aimed at students in general education, not students with special needs. However, all were welldesigned programs with sufficient flexibility to accommodate the instructional needs of a range of learners.…”
Section: The Current Status Of Assistive Technology For Individuals Wmentioning
confidence: 99%